Advancing police use of force research and practice: urgent issues and prospects - Bennell, Craig (Legal and criminological psychology, 2021)
Leading police scholars and practitioners were asked to reflect on the most urgent issues that need to be addressed on the topic of use of force. Four themes emerged from their contributions: use of force and de-escalation training needs to improve and be evaluated; new ways of conceptualizing use of force encounters and better use of force response models need to be developed; the inequitable application of force, and how to remediate biases, needs to be more fully understood; and misconceptions about police use of force need to be identified and corrected. The highlighted topics serve as an agenda for future research. Such research should provide greater insight into when, where, and why force is used by police officers, and how it can be applied appropriately. If implemented, the practical recommendations included in the contributions should have a positive impact on police performance, public trust and confidence in the police, and citizen and officer safety.